The Influence of Environmental Community Order, Government and Policy Support, and Economic Motivation on Participation in Tourism Environmental Conservation - Sitanggang, Holan Dianju Melva; Sitanggang, Eva Rianty Angelina (Journal of Ecohumanism, 2025)
This study analyzes the influence of local community order and government support on participation and policies in preserving the tourist environment with economic motivation as an intervening variable. The research was conducted in Samosir Regency, North Sumatra, from January to June 2024. The research method used a quantitative approach with path analysis techniques. Data were collected from 80 respondents selected using a simple random sampling method. The results showed that local community order, government support, and economic motivation positively and significantly influence participation and tourism environmental conservation policies at the 5% alpha significance level. Economic motivation as an intervening variable also plays an important role in strengthening the relationship between local community order and government support for environmental conservation. This study confirms the importance of collaboration between local communities, government, and economic aspects in creating sustainable tourism. The findings provide practical implications for the formulation of more effective tourism environmental management strategies in Samosir Regency.